Public and family aspects of diagnosis post-traumatic stress disorder at military personnel after return from combat zone - Omelyanovich, Віталій (Psychosomatic Medicine and General Practice, 2019)
Background. In connection with the challenges of modernity, PTSD is a serious problem of general and especially military psychiatry. The diagnosis of "PTSD" is, in the first place, etiologically determined, but both "developmental and clinical assessment of this condition" have such "non-medical" factors as social and family-associated ones. Method. The research material is modern publications devoted to the study of socio-psychological, family and social factors that play a role in shaping PTSD and influence the use of this diagnosis when inspecting. The research method is bibliographic-analytical. Results. According to North American authors, the number of firefighters who received disabilities due to PTSD increased from 1999 to 2004 by 79.5%, while the disability due to other diseases among them grew by only 12 2%. Social disability policy encourages military personnel to receive psychiatric diagnoses, primarily PTSD. In society, the diagnosis of PTSD is often used to justify criminal behavior. Another problem lies in the fact that another part of the military personnel, on the contrary, hide the symptoms of PTSD, fearing the everyday stigmatization of the “mentally ill” and undermining their careers. In addition to societal factors affecting the use of the PTSD diagnosis, important non-medical factors are family aspects of military personnel. The development of PTSD and its transition to the prolonged form are negatively affected by the absence of military personnel at home for more than six months, the impossibility of remote communication with loved ones during the hostilities, the absence of a family, and family-like, ironically, the presence of children in the family. Conclusion. Due to the influence of socially-associated factors, there are certain parts of military personnel involved in the hostilities, one of which is prone to simulating or aggravating the symptoms of PTSD, and the second, on the contrary, is prone to dissimulation of post-stress psychopathological symptoms. Among family factors that should be considered as opportunistic, special attention should be paid to the lack of the possibility of remote communication with relatives during stay in the combat zone, the absence of military personnel at home for more than six months, and the presence of military personnel in their families. To improve the quality of diagnostic and rehabilitation work, it is necessary to conduct a scientifically grounded adaptation of modern foreign psychological tests aimed at diagnosing PTSD and developing specific domestic techniques as soon as possible.